Mathias Casimirus Sarbievius and Baroque Emblem - Šarkauskienė, Skirmantė (Respectus Philologicus, 2006)
One of the most important genres optimally expressing the principles and art trends of the Baroque epoch was the emblem. The literary emblem is an amalgam of pictorial art (ars pictoria) and poetry (ars poetica), conditioning the layer of sense developing in between their synthesis. The present article discusses the main aspects of the relations between the poetical, scenic and prosaic works by Mathias Casimirus Sarbievius (1595-1640) with the Baroque emblemics. The four epigrams called emblems by Sarbievius himself and eulogistic epigrams interpreting heraldic signs reflect the interaction between emblem and armorial poetry, which was the essential feature of the occasional poetry in the Grand Duchy of Lithuania. The most approximate to the canon of emblem genre considering form and contents are the epigrams about Amor divinitus, especially those in which Sarbievius varies the motives of the Canticle. In other cases, it is possible to discuss the emblemical structure and the emblemical treatment of different images. It could be odes with epigraphs from Canticle or those with titles expressing any concrete image, e.g., plant, heraldic sign, biblical or historical character. The influence of the emblem is evident in scenic and prosaic works by Sarbievius, including the theatrical dramatization Hymenodora, declamations Sacra Lithothesis and the libretto for the musical play Silviludia, tractate Dii gentium, sermon Laska marszalkowska. Sarbievius emblemically, i.e., he abundantly uses images from the plastic arsenal of emblems; besides, classical, biblical motives and images, heraldic signs are interpreted by Sarbievius according to conventions of the emblem genre and, this way, assume a new sense.